Triggering receptor expressed on myeloid cells-1 in sepsis, and current insights into clinical studies - Theobald, Vivienne; Schmitt, Felix; Heim, Chiara; Gaißmaier, Lena; Brenner, Thorsten; Weigand, Markus A. (Critical care, 2024)
Triggering receptor expressed on myeloid cells-1 (TREM-1) is a pattern recognition receptor and plays a critical role in the immune response. TREM-1 activation leads to the production and release of proinflammatory cytokines, chemokines, as well as its own expression and circulating levels of the cleaved soluble extracellular portion of TREM-1 (sTREM-1). Because patients with sepsis and septic shock show elevated sTREM-1 levels, TREM-1 has attracted attention as an important contributor to the inadequate immune response in this often-deadly condition. Since 2001, when the first blockade of TREM-1 in sepsis was performed, many potential TREM-1 inhibitors have been established in animal models. However, only one of them, nangibotide, has entered clinical trials, which have yielded promising data for future treatment of sepsis, septic shock, and other inflammatory disease such as COVID-19. This review discusses the TREM-1 pathway and important ligands, and highlights the development of novel inhibitors as well as their clinical potential for targeted treatment of various inflammatory conditions.
Published 09 January 2024
Gesehen am 14.03.2024